From Hermes to Gödel and Guastini: on Hermeneutical Power - Siuffi-Campo, Juan Carlos (Uptc, 2022)
The purpose of this study was to provide a philosophical/conceptual review of hermeneutical power and its role in the legitimation, definition, and conceptualization of institutional and legal discourses. This is done starting from la laguna de Gödel, which demonstrates the importance of constitutional interpretation and provides an approach to Guastini’s definition of judicial activism. There is also a review of the Greek myth of the god Hermes with which an ethical framework of the hermeneutic task is built in order to understand its depth. The discoveries of the Greek myth allow a deeper understanding of the new hermeneutical and jurisprudential trends.